Rediscovering the Poet:: Evelyn Lau - Castelao, Isabel (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2004)
Evelyn Lau discusses the recurring themes of relationships, travel, and place in her poetry. Finding a way to voice the emotional and to critically engage with the confessional mode in poetry is important, and balancing an awareness of form with a concern to avoid rigidity allows the poetry, from one collection to the next, to become increasingly accomplished. For a number of Evelyn Lau's women characters the source of strength comes from seeing, from being observant. Though it is very difficult to lift writing out of two people in a room together, this drama seems one of the most natural vehicles for poetry.